A study of manual toothbrushing skills in children aged 3 to 11 years. - (:unkn) unknown (My University, 2002)
The aim of the study was to evaluate toothbrushing management and ability of children in relation to age and gender. The study population consisted of 75 children and were divided into three equal groups as 3-5, 6-8 and 9-11 years of age. The grip type during toothbrushing was recorded on videotape, The most preferred grip types were distal (73%) followed by power (43%) and oblique grips (29%). There were a statistically significant differences between age groups and the grip types (p < 0.0041) but no significant difference was seen between boys and girls in grip preferences (p > 0.05). The mean duration of toothbrushing was shorter in 3-5 years of age group (28 seconds) than the 6-8 and 9-11 age groups (35 and 47 seconds respectively).